1924
DOI: 10.1172/jci100003
|View full text |Cite
|
Sign up to set email alerts
|

Blood Reaction and Blood Gases in Pneumonia

Abstract: Peabody in 1912 (1) published a paper on the metabolism in pneumonia, in which he reviewed the previous literature and studied among other factors the blood gases and acid-base balance. Since Peabody, a number of other investigators have studied the blood gases and the question of the existence and importance of acidosis in pneumonia. The present paper is a report of observations on these subjects, in which recently developed methods have made possible the attainment of more complete results and apparently hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1924
1924
1993
1993

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…(11). (12) found normal values for pH in pneumonic patients, whereas Leake, Vickers and Brown (13) found slight acidosis in the experimental pneumonia of dogs.…”
Section: Resultsmentioning
confidence: 99%
“…(11). (12) found normal values for pH in pneumonic patients, whereas Leake, Vickers and Brown (13) found slight acidosis in the experimental pneumonia of dogs.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the volume of air in the lungs varied coincidently with the clinical course of the disease, but no unequivocal correlation could be established between lung volume changes and variations in the rate and depth of respirations. A more recent study (4) of the acid-base equilibrium of the blood of patients suffering from lobar pneumonia revealed no changes which could be regarded as responsible for these abnormal respiratory phenomena.…”
Section: Introductionmentioning
confidence: 90%
“…It does, however, not depend upon anoxemia because rapid and shallow breathing persists after anoxemia has been relieved; and because it occurs even when anoxemia has been prevented by previous oxygen inhalation. 4. The cause of rapid and shallow breathing following embolism of the pulmonary arterioles and capillaries is therefore not anoxemia.…”
mentioning
confidence: 99%
“…The latter is, in turn, an indication that the lungs are not efficiently performing their function of oxygenating the blood in the pulmonary circulation. Because of the more rapid diffusion and greater solubility of C02, Van Slyke (5) and others (10) have concluded that before pulmonary impairment can result in clinically serious carbon dioxide retention the most extreme anoxemia must develop. Although these pulmonary cases cannot be said to have CO2 acidosis, they do show a high plasma CO2 and bicarbonate content, which are most easily explained as a response to a retention of carbon dioxide.…”
mentioning
confidence: 99%